Strengthening the capacity of tourism aware groups through citizens journalism assistance as a promotion effort for village tourism labuhan burung village towards tourism 4.0 - Griwandani Griwandani; Hendra Gunawan; Tati Hidayati; L. Kandera Ilham; Khairunnisah; Asrul Fusaini; Rusmi Hasanah; Hasbullah Hasbullah; Najamudin; Wawan Hermansyah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The purpose of this service is to facilitate the availability of trained resources in promoting the tourist village of Labuhan Burung Village, In addition, it can help reduce unemployment through productive activities that can generate a source of income for residents, become a source of Village PAD so that the formation of an independent and independent Labuhan Burung Village prosperous. However, due to the lack of understanding and competence of POKDARAWIS in Labuhan Burung Village in promoting and introducing tourism potential in Labuhan Burung Village, this has become a significant problem and obstacle. The implementation methods in this service are preparation and team consolidation, providing training/assistance in managing citizen journalism, distributing and establishing work divisions, evaluation and monitoring. The results of the implementation of this activity, namely, the implementation of tourism promotion training activities, training on the management of citizen journalism, the dissemination of activities to all target areas. From the implementation of this activity, we can conclude that, there has been a tourism priority program in Labuhan Burung Village, the formation of ready and professional tourism activists. In addition, the promotion of tourism in Labuhan Burung Village is maximized, such as the Village Tourism Facebook, the Labuhan Burung Village Tourism Website, and the establishment of sustainable collaboration between the IISBUD SAREA PHP2D Team and Pokdarwis, the Labuhan Burung Village government, and several related institutions.